2022
DOI: 10.1002/pc.27031
|View full text |Cite
|
Sign up to set email alerts
|

A study on graphene reinforced carbon fiber epoxy composites: Investigation of electrical, flexural, and dynamic mechanical properties

Abstract: In this study, graphene nanoplatelets (GNPs) added to epoxy matrix composite reinforced by aeronautical grade carbon fibers (CFs) were fabricated by the vacuum infusion method, and the effect of different GNPs contents (0.05, 0.25, and 1.25 wt%) on electrical conductivity, flexural properties, and dynamic mechanical properties were investigated. The results revealed an 8-and 73-times improvement in conductivity values across the thickness with the addition of 0.05 and 0.25 wt% GNPs, respectively, compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Based on the conductivity values given in Figure 4, T–T–T electrical conductivities increased more than the surface electrical conductivity values with increasing filler content. This is very similar to those revealed in our previous work 33 for GNPs (0.05–1.25 wt.%)/CFRP composites. The difference in surface and T-T-T conductivity values is indicated by the presence of the RGO filler, which provides conductive paths between the carbon layers 15,33 and aids in the transport of electrons across the matrix-CF networks by reducing the surface resistivity of the epoxy matrix.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the conductivity values given in Figure 4, T–T–T electrical conductivities increased more than the surface electrical conductivity values with increasing filler content. This is very similar to those revealed in our previous work 33 for GNPs (0.05–1.25 wt.%)/CFRP composites. The difference in surface and T-T-T conductivity values is indicated by the presence of the RGO filler, which provides conductive paths between the carbon layers 15,33 and aids in the transport of electrons across the matrix-CF networks by reducing the surface resistivity of the epoxy matrix.…”
Section: Resultssupporting
confidence: 92%
“…Srivastava et al 8 reported an increase in the flexural strength of graphene-CFRP composites prepared by coating the surface-treated fibers with graphene nanoplatelets. More recently, in our previous work, 33 a commercial graphene in different ratios (0.05, 0.25, and 1.25 wt.%) was dispersed in epoxy matrix using a tip sonicator and graphene-added/CFRP composites were produced by vacuum infusion method. We reported that flexural strength was negatively affected after addition of 1.25% wt.…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that the polymer blend composite's modulus increases on increasing the filler loading because of the increment of hardness and compactness. [ 50 ] The pictorial image of the flexible sample is shown in the Figure 2B,C.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations have been made by Liu et al, 39 Kesavulu et al 40 and Rao et al 41 Thus, improvements in the properties are very much possible, provided an excellent bonding exists between the matrix and the reinforcement/ filler, especially using graphene nano-platelets. However, an increase of more than 70% due to the addition of graphene and carbon fibre was observed by Odabsi et al, 42 and severe fibre matrix deboning was also observed at graphene loading of more than 1 wt%, leading to reduced flexural strength. Alok et al 35 research on carbon fiber-based epoxy composites has yielded higher flexural strength for 0.2 GP.…”
Section: Flexural Strength and Modulusmentioning
confidence: 94%